“Patenting of Classic Wastewater Treatment System with Naturally Occurring Organic Materials in the Niger Delta Region of Nigeria” - MOORE, E. N. (European Journal of Applied Sciences, 2022)
The Classic wastewater treatment system (engineered sewage treatment system) was developed and deployed to treat domestic waste (human fasces and urine) water for re-use. Naturally occurring organic materials were used in the treatment process, where 40% of these treatment materials are considered as waste in itself. Effluent from the treatment system was analyzed with physico-chemical and microbial parameters within stipulated limits of WHO/FMENV for safe water use. The removal efficiency of E.Coli, fecal coliform, total coliform, streptococcus and phosphorus from the effluent ranged between 90 to 99% which shows the effectiveness of the treatment system in sewage treatment.